Free Total Rhubarb Anthraquinones Protect Intestinal Injury via Regulation of the Intestinal Immune Response in a Rat Model of Severe Acute Pancreatitis - Xiong, Yuxia; Chen, Li; Fan, Ling; Wang, Lulu; Zhou, Yejiang; Qin, Dalian; Sun, Qin; Wu, Jianming; Cao, Shousong (Frontiers in Pharmacology, 2018)
Intestinal mucosal immune barrier dysfunction plays a key role in the pathogenesis of severe acute pancreatitis (SAP). Rhubarb is a commonly used traditional Chinese medicine as a laxative in China. It markedly protects pancreatic acinar cells from trypsin-induced injury in rats. Free total rhubarb anthraquinones (FTRAs) isolated and extracted from rhubarb display the beneficial effects of antibacteria, antiinflammation, antivirus, and anticancer. The principal aim of the present study was to investigate the effects of FTRAs on the protection of intestinal injury and modification of the intestinal barrier function through regulation of intestinal immune function in rats with SAP. We established a rat model of SAP by injecting 3.5% sodium taurocholate (STC, 350 mg/kg) into the biliopancreatic duct via retrograde injection and treated the rats with FTRAs (36 or 72 mg/kg) or normal saline (control) immediately and 12 h after STC injection. Then, we evaluated the protective effect of FTRAs on intestinal injury by pathological analysis and determined the levels of endotoxin (ET), interleukin 1β (IL-1β), tumor necrosis factor α (TNF-α), nitric oxide (NO), myeloperoxidase (MPO), capillary permeability, nucleotide-binding oligomerization domain-like receptors 3 (NLRP3), apoptosis-associated speck-like protein containing a CARD domain (ASC), casepase-1, secretary immunoglobulin A (SIgA), regulatory T cells (Tregs), and the ratio of Th1/Th2 in the blood and/or small intestinal tissues or mesenteric lymph node (MLN) cells. Moreover, the chemical profile of FTRAs was analyzed by HPLC-UV chromatogram. The results showed that FTRAs significantly protected intestinal damage and decreased the levels of ET, IL-1β, TNF-α, and NO in the blood and TNF-α, IL-1β, and protein extravasation in the intestinal tissues in SAP rats. Furthermore, FTRAs significantly decreased the expressions of NLRP3, ASC, and caspase-1, the number of Tregs and the ratio of Th1/Th2, while significantly increased the expression of SIgA in the intestinal tissues and/or MLN cells in SAP rats. Our results indicate that FTRAs could protect intestinal injury and improve intestinal mucosal barrier function through regulating immune function in SAP rats. Therefore, FTRAs may have the potential to be developed as the novel agent for the treatment of SAP clinically.